An Account of the Musical Performances in Westminster-Abbey and the Pantheon, May 26th, 27th, 29th; and June the 3rd, and 5th. In Commemoration of Handel - Burney, Charles 1726-1814; Burney, Edward Francis 1760-1848 (London Musical Fund Payne Robinson, 1785)
To the King -- Preface -- Sketch of the Life of Handel -- Character of Handel as a Composer -- Chronological List of Handel's Works -- Handel's Music. Proposals for Printing by Subscription, by R. Birchall -- Addenda to the Preface of the Commemoration Account -- Addenda to Life of Handel -- Commemoration of Handel
Lavishly illustrated account in quarto format, containing a biography and works' list of Handel, and proposals for printing a complete edition of his works; the illustrations depict the medal that was struck on the occasion, a view of Handel's monument at Westminster Abbey, the tickets of admission to the performances, a view of the orchestra and audience, a plan of the chorus and orchestra
Ex libris Thomas Robinson Sherburn (ms.)
Keywords: Handel, George Frideric -- 1685-1759; Westminster Abbey (London, United Kingdom); 18th Century (1701-1800); Music history; Biography; London (United Kingdom)